Victims of Ecological Crime : (Massive and Intensive Victimization) (Kriminalističke teme, 2002)
Since the beginning of mankind there was never more drastic and threatening danger on the planet. What we see is not only the use, but more and more the abuse as well, of various technological achievements, and essential changes in atmosphere, hydrosphere and lithosphere/ which give conditions for the life on earth/as the most precious good of nature. Negative tendencies are increasing, bringing into a direct danger the life on planet. One should emphasizes threat the 20th century is marked with a very intensive crashes and brakes, bigger then in the previous history of mankind. What is in question is mainly culmination and anthology of human evil. With violent burdens and especially emphasized problems, we are getting into the third millennium, without the solution for this problem in sight. „In case we do not solve the accumulated burdens of negativities from the 20th century in the first decade of the 21st century, humankind from the catastrophe could be save only the Almighty.“, explicitly and clearly says Ivan Supek13. Or what with a special reason emphasized a great poet Enes Kisevic, only because of the big fighters in the maintenance of humankind „The Almighty still maintains the world. Only in these pure people the nature could with its face see its aureole as well. And that is the purpose of human existence on earth.“